ESG Scores as Indicators of Green Business Strategies and Their Impact on Financial Performance in Tourism Services: Evidence from Worldwide Listed Firms - Chrysoula Matsali; Michalis Skordoulis; Aristidis Papagrigoriou; Petros Kalantonis (Administrative Sciences)
The increasing integration of Environmental, Social, and Governance (ESG) practices into corporate strategy has raised important questions about their financial implications. This study examines the relationship between ESG performance and financial outcomes in the tourism industry, an industry that is both highly visible and environmentally sensitive. To achieve this, this study analyzes the impact of the three ESG dimensions on financial performance, measured by Return on Assets (ROA). Using panel data econometric techniques, this study examines a balanced panel dataset of 154 listed tourism services firms between 2017 and 2021 to assess how each ESG pillar influences profitability. ESG data were sourced from Refinitiv Eikon, a widely validated provider in ESG-financial research. The analysis employs panel data econometric techniques with firm size and leverage as control variables. Our findings indicate that the Environmental, Social, and Governance scores each have a statistically significant negative effect on ROA, while the ESG controversies score is not statistically significant. These results suggest that despite the reputational value of ESG engagement, its short-term financial impact may be limited or negative in capital-intensive service sectors, such as tourism. This study contributes to the literature by providing sector-specific, post-crisis empirical evidence and highlights the need for a nuanced understanding of ESG–financial dynamics across industries.